Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China - Li, Weihai; Pan, Zhaohui; Liu, Ruijun (Zootaxa, 2017)
A new stonefly species of the chloroperlini genus Sweltsa, S. tibetensis, sp. n. is described from the southeastern Tibet Autonomous Region, China and its taxonomic relationship to related taxa is discussed.